CD4 T-Cell Responses in Primary HIV Infection: Interrelationship with Immune Activation and Virus Burden - Chevalier, Mathieu F.; Didier, Céline; Girard, Pierre-Marie; Manea, Maria E.; Campa, Pauline; Barré-Sinoussi, Françoise; Scott-Algara, Daniel; Weiss, Laurence (Frontiers in Immunology, 2016)
Early events during primary HIV infection (PHI) are thought to influence disease outcome. Although a growing body of evidence suggests a beneficial role of HIV-specific CD4 help in HIV infection, it is unclear how early viral replication, systemic immune activation and antiretroviral therapy (ART) may shape CD4 T-cell responses during PHI, and whether HIV-specific CD4 responses contribute to the high immune activation observed in PHI. Twenty-seven patients with early PHI were included in a prospective longitudinal study and twelve of them received ART after enrollment. Fresh PBMC were used for measurement of ex-vivo T-cell activation and of cytokine-producing CD4 T-cells following stimulation with PMA/ionomycin or HIV-1-gag-p24 antigen. Patients were segregated based on CD8 T-cell activation level (i.e. %HLA-DR+CD38+ CD8 T-cells) at baseline. Patients with lower immune activation exhibited higher frequency of bulk CD4 T-cells producing IFN-γ or IL-17, and higher effector-to-regulatory cell ratios. No differences were found in HIV-specific CD4 T-cell frequencies. In contrast, segregation of patients based on plasma-viral load (pVL) revealed that patients with higher pVL showed higher cytokine-producing HIV-specific CD4 responses. Of note, the frequency of IFN-γ+ HIV-specific CD4 T cells significantly diminished between baseline and month-6 only in ART-treated patients. However, early treatment initiation was associated with better maintenance of HIV-specific IFN-γ+ CD4 T-cells. These data suggest that HIV-specific CD4 responses do not fuel systemic T-cell activation, and are driven by viral replication but not able to contribute to its control in the early phase of infection. Moreover, our data also suggest a benefit of early treatment for the maintenance of HIV-specific CD4 T-cell help.